The Relationship Between Dragon Fruit Consumption and Hb Levels in Adolescent Girls Aged 13 to 14 Years at Public Yunior High School-4 Lemo - Bella Monika Friskila; Widia Shofa Ilmiah (Jurnal Ventilator, 2025)
Anemia remains a common nutritional problem among adolescent girls, particularly during early adolescence when iron requirements increase due to rapid growth and the onset of menstruation. This study aimed to analyze the effect of dragon fruit consumption on hemoglobin levels among adolescent girls aged 13–14 years at SMPN 4 Lemo. An analytical observational study with a pre–post design was conducted involving 30 adolescent girls selected through total sampling. Dragon fruit consumption was administered, and hemoglobin status was measured before and after the intervention. Data were analyzed using univariate analysis and the Wilcoxon Signed-Rank Test. The results showed that before dragon fruit consumption, most respondents were classified as anemic. After the intervention, the majority of respondents experienced an improvement in hemoglobin status, shifting from anemia to normal levels. The Wilcoxon Signed-Rank Test indicated a statistically significant difference in hemoglobin levels before and after dragon fruit consumption (p < 0.05). These findings demonstrate that dragon fruit consumption is associated with an improvement in hemoglobin levels among adolescent girls. In conclusion, dragon fruit consumption has the potential to be used as a local food–based nutritional intervention to improve hemoglobin status and reduce anemia among early adolescent girls. However, further studies with stronger research designs and control of confounding factors are recommended to confirm a causal relationship.